Inertial flywheel resistance training and muscle oxygen saturation - Timon, R.; Ponce-Gonzalez, J. G.; Gonzales-Montesinos, J. L.; Olcina, G.; Perez-Perez, A.; Castro-Pinero, J. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The inertial flywheel device causes an increase in eccentric overload during training. The aim was to study muscle oxygen saturation produced during an inertial flywheel squat training, comparing it with a barbell squat training. METHODS: Twelve male adults performed a barbell squat training (3×8 reps, 75-80% 1RM) and a flywheel squat training (3×8 reps, all-out). Muscle oxygen saturation (%SmO2), total hemoglobin (tHb), reoxygenation, heart rate (HR), lactate, vertical jumps, maximal voluntary isometric contraction and rated perceived exertion (RPE) were studied. RESULTS: Both protocols produced a significant decrease in %SmO2 and tHB during the sets of squats, and a significant increase in HR, lactates dand RPE after training. The flywheel squat protocol caused a greater decrease in %SmO2 than the barbell squat protocol in each of the sets of exercises (1st set: -67.5±7.2% vs. -53.7±16.2%; 2nd set: -67.2±13.5% vs. -53.6±15.4%; 3rd set: -68.1±13.0% vs. -55.0±17.0%), as well as a longer reoxygenation after finishing the training (61.7±12.6 vs. 55.7±13.7 s). CONCLUSIONS: Although no differences were found on a muscle fatigue level, the flywheel training brought on greater physiological stress than the barbell squat training, observing a greater decrease in muscle oxygen saturation and a longer reoxygenation.